2017
DOI: 10.1128/iai.00939-16
|View full text |Cite
|
Sign up to set email alerts
|

Differential Macrophage Polarization from Pneumocystis in Immunocompetent and Immunosuppressed Hosts: Potential Adjunctive Therapy during Pneumonia

Abstract: We explored differential polarization of macrophages during infection using a rat model of Pneumocystis pneumonia. We observed enhanced pulmonary M1 macrophage polarization in immunosuppressed (IS) hosts, but an M2 predominant response in immunocompetent (IC) hosts following Pneumocystis carinii challenge. Increased inflammation and inducible nitric oxide synthase (iNOS) levels characterized the M1 response. However, macrophage ability to produce nitric oxide was defective. In contrast, the lungs of IC animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 69 publications
3
48
0
Order By: Relevance
“…Other studies have implicated Type 1 and Type 2 immunity in protecting against Pneumocystis infection. Some studies have correlated robust Type 2 responses and M2‐polarized macrophage responses with protection against Pneumocystis and fungal killing . Conversely, artificial induction of IFN‐ γ responses during Pneumocystis infection in the absence of CD4 T‐cell help restores control of infection, suggesting that Type 1 responses at least have the potential to mediate protection against Pneumocystis .…”
Section: Type 1 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…Other studies have implicated Type 1 and Type 2 immunity in protecting against Pneumocystis infection. Some studies have correlated robust Type 2 responses and M2‐polarized macrophage responses with protection against Pneumocystis and fungal killing . Conversely, artificial induction of IFN‐ γ responses during Pneumocystis infection in the absence of CD4 T‐cell help restores control of infection, suggesting that Type 1 responses at least have the potential to mediate protection against Pneumocystis .…”
Section: Type 1 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…In contrast, rats with a competent immune response had a more prominent alternative macrophage (M2) response and cleared infection. Treatment of immunosuppressed rats with M2 cells reverted rats to a protected phenotype [33, 34]. …”
Section: The Role Of Cell-mediated Adaptive Immunitymentioning
confidence: 99%
“…Th2 responses to Pneumocystis drive an allergic reaction in healthy hosts. APCs = antigen presenting cells, Th = T helper, M1 = classically activated macrophages, M2 = alternatively activated macrophages [9, 10, 32, 34, 39]. …”
Section: Figurementioning
confidence: 99%
“…Alternatively activated M2 macrophages are associated with Pc clearance ( 13 ) and possess anti-Pc effector function ( 14 ), which may represent a critical mechanism by which CD4 + T cells modulate macrophage function for effective host defense. A recent study found that AMs from Pc-susceptible immunosuppressed hosts adopt a classically activated M1 phenotype, while those from immunocompetent hosts adopt an M2 phenotype following Pc infection ( 15 ). These investigators also determined that the adoptive transfer of either M1 or M2 macrophages to Pc-infected immunosuppressed hosts enhanced Pc clearance, but less inflammation and better outcomes were observed following M2 transfer.…”
Section: Introductionmentioning
confidence: 99%